PENGEMBANGAN MODUL FISIKA TOPIK GEJALA GELOMBANG DI SEKOLAH MENENGAH ATAS (SMA) NEGERI 3 JAYAPURA - Rustamaji, .; Triwiyono, . (Jurnal Ilmu Pendidikan Indonesia, 2013)
This research aimed at creating module physics with the topic waves phenomena that was relevant to be used at school that carry out a system of sks. The method used was research and development with phases: preliminary study (define), program designing (design) and development (develop). The module design was based on the result of the preliminary study. Then the program was judged by experts and pilot tested on thirty students of XI class of Senior High school 3 Jayapura, using one group pretest-posttest design. Then wider scale tryout using a non-equivalent group pretest-posttest quasi experimental design, and was conducted on sixty one students at the same school. Conclusions of the research were 1) characteristics of the module physics with the topic waves phenomena, among others, self instructional, self contained, stand alone, adaptive, and user friendly. 2) the application of physics module waves phenomena in the learning topics can significantly improve students mastery of concepts, 3) prominence of waves phenomena, among others, have a complete module structure, equipped with the learner worksheets, complete with mathematical equations, and smart solution. 4) a limitation of this module is not equipped with an exercise problems. Keywords: Research, physics module, students, phenomena.